Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Openjoylumbangaol (Skena Bisnis, 2025)
The purpose of this study is to analyze the influence of tax planning and deferred tax expenses on earnings management. The data obtained is secondary data from manufacturing companies listed on the Indonesia Stock Exchange. The research method used is descriptive quantitative research. The sample was selected using purposive sampling method. The population of this study consists of 228 manufacturing companies listed on the Indonesia Stock Exchange, with a sample of 77 companies over four years, from 2019 to 2022. The type of data used in this study is secondary data in the form of financial statements obtained through the website www.idx.co.id. The data analysis technique used is panel data analysis using Eviews 12. The results of this study indicate that partially, the variables of tax planning, deferred tax expenses, and company size influence earnings management. Simultaneously, the variables of tax planning, deferred tax expenses, and company size influence earnings management.